When Are Agenda Setters Valuable?. Issue 1 (26th July 2017) - Fouirnaies, Alexander
Abstract: Why do industries donate money to legislative campaigns when roll‐call votes suggest that donors gain nothing in return? I argue that corporate donors may shape policy outcomes by influencing powerful agenda setters in the early stages of lawmaking. On the basis of a new data set of more than 45, 000 individual state legislator sessions (1988–2012), I document how agenda control is deemed valuable to legislators and groups seeking influence on policy. Employing a difference‐in‐differences design, I assess the revealed price, as measured by campaign contributions, that firms are willing to pay for access to committee and party leaders and document how this price varies across industries and institutions. The results indicate that industries systematically funnel money to the legislative agenda setters by whom they are regulated, and to those endowed with important procedural powers. I document that the value of agenda‐setter positions has increased dramatically in recent years. Finally, exploiting changes in state laws, I show that relaxing contribution limits significantly benefits committee chairs and party leaders more so than it does other legislators, suggesting that agenda setters have strong incentives to obstruct restrictive campaign finance reforms.